2007
DOI: 10.1159/000107707
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Response to Pegylated Interferon and Ribavirin in Hepatitis C by Polymorphisms in the Viral Core Protein and Very Early Dynamics of Viremia

Abstract: Objective: To evaluate power of amino acid polymorphisms in core protein of hepatitis C virus (HCV) for predicting sustained virological response (SVR) to pegylated interferon (Peg-IFN)/ribavirin, when they were combined with virological response. Methods: Peg-IFN/ribavirin was given to 118 patients infected with HCV genotype 1b in high viral loads. Amino acid polymorphisms (Arg70 vs. Gln70 and Leu91 vs. Met91) in combination with on-treatment virological responses were correlated with SVR. Results: End-of-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 70 publications
3
54
1
Order By: Relevance
“…After multivariate analysis, EVR and adherence to peg-IFN were demonstrated to be associated with SVR. Of the baseline factors assessed before treatment, age, sex, WBC, α-feto protein level, γ-glutamyl transpeptidase, and LDL-cholesterol have been re por ted to be associated with a high SVR rate following peg-IFNα-2b plus RBV therapy in CHC Japanese patients [8,11,12] . The results of this study were very similar to those of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After multivariate analysis, EVR and adherence to peg-IFN were demonstrated to be associated with SVR. Of the baseline factors assessed before treatment, age, sex, WBC, α-feto protein level, γ-glutamyl transpeptidase, and LDL-cholesterol have been re por ted to be associated with a high SVR rate following peg-IFNα-2b plus RBV therapy in CHC Japanese patients [8,11,12] . The results of this study were very similar to those of our study.…”
Section: Discussionmentioning
confidence: 99%
“…The HCV strain and the efficacy of interferon treatment vary between races and countries [6,7] . Identification of the factors associated with treatment efficacy is extremely impor tant, however, few studies involving large populations have reported on the treatment of Japanese CHC patients with pegylated interferon alpha-2b (peg-IFNα-2b) plus RBV [8,9] . In this study, we evaluated the efficacy and safety of peg-IFNα-2b plus RBV therapy in CHC genotype Ib patients with a high viral load.…”
Section: Introductionmentioning
confidence: 99%
“…The 8-kDa (p8) minicore protein was also detected in Huh-7.5 cells supporting full-length genotype 1b neomycin-selectable replicons. Expression of p8 was enhanced in replicons with a U271A mutation in codon 91 that confers clinically significant interferon resistance (1)(2)(3). Experiments with in vitro transcripts revealed that p8 synthesis is not dependent on the synthesis of the mature p21 core protein and occurs in 293T cells transfected with transcripts in which the AUG of the main reading frame has been replaced by a UAG stop codon.…”
mentioning
confidence: 99%
“…Amino acid substitutions of core aa 70 and 91 and within the NS5A ISDR, as well as genetic polymorphisms in the host IL28B gene, encoding IFN--3 on chromosome 19, affect the outcome of interferon-based therapies for chronic hepatitis C patients (1,2,9,10,16,40,43). Even if only the amino acid substitution of a major variant were assumed, an accurate therapeutic effect would be impossible to predict.…”
Section: Discussionmentioning
confidence: 99%